Executive leadership in Anglo-American systems - Campbell, Colin, 1943 June 10-; Wyszomirski, Margaret Jane (Pittsburgh, Pa. : University of Pittsburgh Press, 1991)
In this collection, eighteen distinguished scholars and practicing officials address the problems of contemporary executive leadership in the United States, Britain, Canada, and Australia. Essays focus on cabinet government; domestic, military, and economic advisers; executive agencies; and personal staff for presidents and prime ministers. Provocative comparisons between and among systems make the discussions particularly insightful.
15. White House Staffing: Salvation, Damnation, and Uncertainty / Joseph A. Pika -- 16. New and Old Lessons on White House Management / Samuel Kernell -- 17. Support for Prime Ministers: A Comparative Perspective / Patrick Weller -- 18. The Role of Press Secretaries on Chief Executive Staffs in Anglo-American Systems / Colin Seymour-Ure.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Presidents -- United States; Presidents -- United States -- Staff; Executive departments -- United States; Cabinet system -- Great Britain; Cabinet system -- Canada; Comparative government; Presidents -- United States -- Employees; Présidents -- États-Unis.; Présidents -- États-Unis -- Personnel; Ministères -- États-Unis.; Cabinet -- Grande-Bretagne.; Cabinet -- Canada; Institutions politiques comparées.; comparative politics; POLITICAL SCIENCE / General; Cabinet system; Comparative government; Executive departments; Presidents; Presidents -- Staff; Canada; Great Britain; United States; Aufsatzsammlung; Regierung; Angloamerika; Political structure and processes; Central government; Aufsatzsammlung